Step
*
1
of Lemma
Taylor-series-converges-everywhere
.....assertion..... 
1. a : ℝ
2. F : ℕ ⟶ ℝ ⟶ ℝ
3. ∀k:ℕ. ∀x,y:ℝ.  ((x = y) 
⇒ (F[k;x] = F[k;y]))
4. infinite-deriv-seq((-∞, ∞);i,x.F[i;x])
5. ∀r:{r:ℝ| r0 ≤ r} . lim k→∞.r^k * (F[k + 1;x]/r((k)!)) = λx.r0 for x ∈ (-∞, ∞)
6. m : ℕ+
7. [%4] : icompact([r(-m), r(m)])
⊢ ∃t:{t:ℝ| r0 < t} . [r(-m), r(m)] ⊆ (a - t, a + t) 
BY
{ (D 0 With ⌜r(m + 1) + |a|⌝  THEN Auto) }
1
.....wf..... 
1. a : ℝ
2. F : ℕ ⟶ ℝ ⟶ ℝ
3. ∀k:ℕ. ∀x,y:ℝ.  ((x = y) 
⇒ (F[k;x] = F[k;y]))
4. infinite-deriv-seq((-∞, ∞);i,x.F[i;x])
5. ∀r:{r:ℝ| r0 ≤ r} . lim k→∞.r^k * (F[k + 1;x]/r((k)!)) = λx.r0 for x ∈ (-∞, ∞)
6. m : ℕ+
7. icompact([r(-m), r(m)])
⊢ r(m + 1) + |a| ∈ {t:ℝ| r0 < t} 
2
1. a : ℝ
2. F : ℕ ⟶ ℝ ⟶ ℝ
3. ∀k:ℕ. ∀x,y:ℝ.  ((x = y) 
⇒ (F[k;x] = F[k;y]))
4. infinite-deriv-seq((-∞, ∞);i,x.F[i;x])
5. ∀r:{r:ℝ| r0 ≤ r} . lim k→∞.r^k * (F[k + 1;x]/r((k)!)) = λx.r0 for x ∈ (-∞, ∞)
6. m : ℕ+
7. [%4] : icompact([r(-m), r(m)])
⊢ [r(-m), r(m)] ⊆ (a - r(m + 1) + |a|, a + r(m + 1) + |a|) 
Latex:
Latex:
.....assertion..... 
1.  a  :  \mBbbR{}
2.  F  :  \mBbbN{}  {}\mrightarrow{}  \mBbbR{}  {}\mrightarrow{}  \mBbbR{}
3.  \mforall{}k:\mBbbN{}.  \mforall{}x,y:\mBbbR{}.    ((x  =  y)  {}\mRightarrow{}  (F[k;x]  =  F[k;y]))
4.  infinite-deriv-seq((-\minfty{},  \minfty{});i,x.F[i;x])
5.  \mforall{}r:\{r:\mBbbR{}|  r0  \mleq{}  r\}  .  lim  k\mrightarrow{}\minfty{}.r\^{}k  *  (F[k  +  1;x]/r((k)!))  =  \mlambda{}x.r0  for  x  \mmember{}  (-\minfty{},  \minfty{})
6.  m  :  \mBbbN{}\msupplus{}
7.  [\%4]  :  icompact([r(-m),  r(m)])
\mvdash{}  \mexists{}t:\{t:\mBbbR{}|  r0  <  t\}  .  [r(-m),  r(m)]  \msubseteq{}  (a  -  t,  a  +  t) 
By
Latex:
(D  0  With  \mkleeneopen{}r(m  +  1)  +  |a|\mkleeneclose{}    THEN  Auto)
Home
Index